Detection of compounds in airborne particles using ion exchange
Patent Information
- Application Number
- JP2022564534
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-05
- Filing Date
- 2021-04-23
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-04-23
AI Technical Summary
【0008】 以上に本発明の数々の特徴のうちでも重要度の比較的高い特徴についてかなり大まかに概説したが、これは、以下に提示する本発明の詳細説明を理解し易くし、また、当業界への本発明の貢献を認識し易くするためである。本発明のその他の特徴は、以下に提示する本発明の詳細説明を添付図面及び請求の範囲の記載と共に参照することでより明瞭に理解することができ、また本発明を実施することで体得できるであろう。
Smart Images

Figure 0007637394000061 
Figure 0007637394000062 
Figure 0007637394000063
Abstract
Description
Related Applications
[0001] This patent application claims priority to U.S. Provisional Patent Application No. 63 / 014,879, filed April 24, 2020, and to U.S. Provisional Patent Application No. 63 / 061,478, filed August 5, 2020, the disclosures of which are incorporated herein by reference.
[0002] U.S. Federal Government Rights This invention was made with government support under Grant No. 70RSAT18C00000018 and Grant No. 70RSAT19C00000016 awarded by the Department of Homeland Security. The Federal Government has certain rights in this invention. [Background technology]
[0003] Opiate abuse is now a public health emergency due to the rise in opiate addiction and the resulting increase in opiate-related deaths. For example, there has been a seven-fold increase in the number of fentanyl confiscations or seizures, which indicates that many overdoses occur due to the availability of fentanyl without a doctor's prescription. Exposure to as little as 2-3 mg of fentanyl has been known to be fatal, and emergency responders are among those at risk of exposure. First responders responding to emergency calls for fentanyl or other drugs laced with fentanyl are at risk of overdosing by inhaling fentanyl. Many of the traditional methods for identifying fentanyl require direct contact with the sample. Non-contact methods are expensive and require large equipment. Therefore, a device to identify fentanyl that is wearable, does not require contact with unknown substances, is sensitive, selective, provides rapid results, and is low cost could be extremely beneficial to first responders. Summary of the Invention [Problem to be solved by the invention]
[0004] More generally, determining the chemical composition of airborne particles is a current challenge: for example, smoke detectors that operate based on light scattering cannot be installed in bathrooms because they cannot distinguish between smoke particles and water particles (steam).
[0005] The methods used to detect airborne chemicals include particle counters, chemical sensors, and analytical instruments. Most particle counters use optical sensors to measure the scattering of light by particles, and are agnostic to the type of particle, measuring water particles as well as other particles. This method generally detects any particle within a certain size range, and does not provide information about the chemical composition of the particle. Most chemical sensors detect molecules based on a measurable signal (e.g., frequency, voltage, conductivity, etc.). Chemical sensors generally do not respond to particles, because the particles have a small contact area with the sensor. Furthermore, most chemical sensors are contained in a housing that prevents particles from reaching the chemical sensor. Analytical instruments often use spectrophotometric or spectroscopic techniques to detect molecules, and are used in laboratories, where samples are pretreated. Analytical methods, such as mass spectroscopy, require expensive equipment (over $100,000) and sample pretreatment. In this method, the particles must first be collected and brought to a laboratory. The particles are then pretreated, which involves breaking them down into their component molecules. This can be done, for example, by laser ablation or chemical extraction. This analytical method is highly accurate and reliable, but it is also expensive, burdensome to the user, not portable, and requires the user to be familiar with chemistry. Other methods are based on Raman spectroscopy (e.g., Thermo Fisher Scientific's (USA) handheld drug analyzer called "THERMO SCIENTIFIC TRUNARC" (THERMO SCIENTIFIC and TRUNARC are trademarks). This type of device is highly portable, suitable for detecting powder-like substances, and does not require breaking down the sample into its component molecules. However, this type of device is not suitable for detecting airborne particles with high sensitivity, and is inevitably expensive. [Means for solving the problem]
[0006] The present disclosure describes a sensor and method for detecting solid particles of a particular salt, such as a salt of fentanyl. According to some embodiments, a sensor for detecting solid particles of a target salt comprises a support substrate, an adsorption layer, a sensitive layer located between the support substrate and the adsorption layer, and a pair of electrodes connected to the sensitive layer and separated from each other by the sensitive layer. The adsorption layer comprises an ion exchange medium formed of a first multiporous material functionalized with a basic or acidic functional group. The basic functional group is capable of removing an acid component from the target salt to generate a free base of the target salt. In the case of an acidic functional group, the acidic functional group is capable of removing a base component from the target salt to generate a free acid of the target salt. The sensitive layer comprises a second multiporous material functionalized to detect the free base or the free acid of the target salt by a change in electrical conductivity.
[0007] The present disclosure further describes a method for detecting solid particles of a target salt. According to one embodiment, the method for detecting solid particles of a target salt comprises exposing an adsorption layer to a gaseous medium containing particles of the target salt. The adsorption layer comprises an ion exchange medium formed of a first multiporous material functionalized with basic or acidic functional groups. The basic or acidic functional groups are adapted to remove an acid or base moiety from the target salt to generate a free base or free acid of the target salt. The free base or free acid of the target salt migrates by diffusion to a sensitive layer adjacent to the adsorption layer. The sensitive layer comprises a second multiporous material functionalized to detect the free base or free acid of the target salt. In particular, the free base or free acid of the target salt changes the electrical conductivity of the second multiporous material. The method further comprises measuring the change in electrical conductivity of the sensitive layer using a pair of electrodes connected to the sensitive layer and separated from each other by the sensitive layer. The pair of electrodes and the sensitive layer may be directly connected, but may also be electrically connected via a conductor disposed between them. According to some further embodiments, the free base is a vapor or gas. According to some embodiments, the concentration of the target salt contained in the gas medium is 0.1 mg / m 3 ~100 mg / m 3 and in some cases 1 mg / m 3 ~4 mg / m 3 It is.
[0008] The above has outlined, rather broadly, some of the more important features of the present invention in order to facilitate understanding of the detailed description of the invention that follows, and to facilitate an appreciation of the present contribution to the art. Other features of the present invention will be more clearly understood from the detailed description of the invention that follows, taken in conjunction with the accompanying drawings and appended claims, or may be learned by the practice of the invention. [Brief description of the drawings]
[0009] [Figure 1]FIG. 1 is a schematic cross-sectional side view of a sensor according to an embodiment of the present disclosure. [Diagram 2] 1A to 1D are schematic top views and cross-sectional side views of a sensor according to an embodiment of the present disclosure. [Diagram 3] 1A and 1B are a schematic top view and a cross-sectional side view of a sensor according to an embodiment of the present disclosure. [Figure 4] A-F are diagrams showing an overall overview of the sensor's operation in detecting fentanyl. In A-B, fentanyl particles enter the sensor. In C-D, the particles are adsorbed onto the nanofibers in the adsorbent layer functionalized with basic functional groups. When the particles come into contact with the adsorbent layer and disturb the nanofibers, a small signal output can be recorded. In E-F, the nanofibers functionalized with basic functional groups have ion-exchange interactions with the fentanyl salt, converting the fentanyl molecule to the free base form. If the free base form of fentanyl migrates and some of it reaches the sensitive layer, a signal output is generated due to the charge transfer in the sensitive layer. [Diagram 5] FIG. 2 is a schematic diagram of a sensor according to another embodiment of the present disclosure. [Figure 6] Figures 6A to 6D show the chemical structures of the nanofibers combined with scanning electron microscope (SEM) images of bis(N-hexylamine) nanofibers (Figure 6A), bis(N-ethylethylamine) nanofibers (Figure 6B), bis(N-propylpropylamine) nanofibers (Figure 6C), and bis(N,N-dimethylbutylamine) nanofibers (Figure 6D). All of the SEM images are at the same magnification. [Figure 7A] 1 is an SEM image of a sensitive layer formed of nanofibers coated on an electrode. [Figure 7B] This is an SEM image of the sensitive layer formed with nanofibers after a second coating process was performed using only ethanol without the use of nanofibers. [Figure 8A] FIG. 1 is an SEM image of an adsorption layer formed from nanofibers of bis-N-N-dimethylhexylamine as a comparative sample. [Figure 8B] 1 is an SEM image of a comparative sample sensitive layer formed of nanofibers of bis-NN-dimethylhexylamine. [Figure 8C] This is an SEM image of a bilayer formed by adsorption of 1 μg of nanofibers. [Figure 8D] The SEM images of the bilayer formed by the adsorption layer of 3 μg of nanofibers are shown in circles, where the sensitive layer is visible through the voids in the adsorption layer. Note that all SEM images shown in Figures 8A to 8D are at the same magnification. [Figure 9A] SEM image of an adsorption layer formed of 1 μg of bis-butylamine nanofibers on top of the nanofibers of the sensitive layer. The area where the nanofibers of the sensitive layer are visible below the adsorption layer is circled. [Figure 9B] 1 is a SEM image of an adsorption layer formed of 3 μg of bis-butylamine nanofibers on the nanofibers of the sensitive layer. [Figure 9C] 9A to 9C are SEM images of nanofibers in the sensitive layer, and all the SEM images shown in Fig. 9A to 9C are at the same magnification. [Figure 10A] SEM image of an adsorption layer formed of 1 μg of bis-(N-ethylethylamine) nanofibers on top of the nanofibers of the sensitive layer. The area where the nanofibers of the sensitive layer are visible below the adsorption layer is indicated by an oval. [Figure 10B] This is an SEM image of an adsorption layer formed by 3 μg of bis-(N-ethylethylamine) nanofibers on the nanofibers of the sensitive layer. [Figure 10C] 10A to 10C are SEM images of nanofibers in the sensitive layer, and all of the SEM images shown in Fig. 10A to 10C are at the same magnification. [Figure 11] FIG. 2 shows the molecular structures of nanofibers of the sensitive layer and nanofibers of the adsorptive layer according to some embodiments used in a sensor array card according to some embodiments. [Figure 12]FIG. 1 shows fentanyl and fentanyl simulants; 1 is fentanyl hydrochloride, 2 is norfentanyl hydrochloride, 3 is propenamido-2-methyl-N-[1-(phenylmethyl)-4-piperidinyl], 4 is propenamido-N-[1-[2-(4-hydroxyphenyl)methyl]-4-piperidinyl]-N-phenyl, and 5 is benzylfentanyl. [Figure 13A] This figure shows the sensor response of a bilayer sensor having a bilayer consisting of an active layer of compound 2 and an adsorption layer of compound 4, with the adsorption layer formed from 1 μg of nanofiber, and a similar bilayer sensor having an adsorption layer formed from 3 μg of nanofiber, when exposed to fentanyl simulants at concentrations of 1 to 2 mg / m3. [Figure 13B] This figure shows the sensor response of a bilayer sensor having a bilayer consisting of a sensitive layer of compound 2 and an adsorption layer of compound 4, with the adsorption layer formed from 1 μg of nanofiber, and a similar bilayer sensor having an adsorption layer formed from 3 μg of nanofiber, when exposed to fentanyl simulants at concentrations of 2 to 4 mg / m3. [Figure 13C] This figure shows the sensor response of a bilayer sensor having a bilayer consisting of an active layer of compound 2 and an adsorption layer of compound 4, with the adsorption layer formed from 1 μg of nanofiber, and a similar bilayer sensor having an adsorption layer formed from 3 μg of nanofiber, when exposed to fentanyl simulants at concentrations of 8 to 16 mg / m3. [Figure 14A] FIG. 2 shows the concentration dependence of a bilayer sensor having a bilayer consisting of a sensitive layer of compound 2 and an adsorbed layer of compound 3. [Figure 14B] FIG. 2 shows the concentration dependence of a bilayer sensor with a bilayer consisting of a sensitive layer of compound 2 and an adsorbed layer of compound 4. [Figure 14C] FIG. 2 shows the concentration dependence of a bilayer sensor with a bilayer consisting of a sensitive layer of compound 2 and an adsorbed layer of compound 5. [Figure 15] FIG. 1 shows fentanyl chain cleavers that were tested to determine sensor response caused by interfering substances. [Figure 16A]This figure shows the sensor response to metamizole at concentrations of 10 to 20 mg / m3 for a comparative sensor using only compound 2, a comparative sensor using only compound 3, a bilayer sensor having a bilayer of compounds 2 / 3, each layer formed from 1 μg of nanofiber, and a bilayer sensor having a bilayer of compounds 2 / 3, each layer formed from 3 μg of nanofiber. [Figure 16B] This figure shows the sensor response to metamizole at concentrations of 10 to 20 mg / m3 for a comparative sensor using only compound 2, a comparative sensor using only compound 4, a bilayer sensor having a bilayer of compounds 2 / 4, each layer formed from 1 μg of nanofiber, and a bilayer sensor having a bilayer of compounds 2 / 4, each layer formed from 3 μg of nanofiber. [Figure 16C] This figure shows the sensor response to metamizole at concentrations of 10 to 20 mg / m3 for a comparative sensor using only compound 2, a comparative sensor using only compound 5, a bilayer sensor having a bilayer of compounds 2 / 5, each layer formed from 1 μg of nanofiber, and a bilayer sensor having a bilayer of compounds 2 / 5, each layer formed from 3 μg of nanofiber. [Figure 17A] This figure shows the sensor response to mannitol at concentrations of 10 to 20 mg / m3 for a comparative sensor using only compound 2, a comparative sensor using only compound 3, a bilayer sensor having a bilayer of compounds 2 / 3, each layer formed from 1 μg of nanofiber, and a bilayer sensor having a bilayer of compounds 2 / 3, each layer formed from 3 μg of nanofiber. [Figure 17B] FIG. 1 shows the sensor response to mannitol at concentrations of 10 to 20 mg / m3 for a comparative sensor using only compound 2, a comparative sensor using only compound 4, a bilayer sensor having a bilayer of compounds 2 / 4, each layer formed from 1 μg of nanofiber, and a bilayer sensor having a bilayer of compounds 2 / 4, each layer formed from 3 μg of nanofiber. [Figure 17C]FIG. 1 shows the sensor response to mannitol at concentrations of 10 to 20 mg / m3 for a comparative sensor using only compound 2, a comparative sensor using only compound 5, a bilayer sensor having a bilayer of compound 2 / 5, each layer formed from 1 μg of nanofiber, and a bilayer sensor having a bilayer of compound 2 / 5, each layer formed from 3 μg of nanofiber. [Figure 18A] FIG. 1 shows the sensor response to α-D-lactose at concentrations of 10 to 20 mg / m3 for a comparative sensor using only compound 2, a comparative sensor using only compound 3, a bilayer sensor having a bilayer of compounds 2 / 3, each layer formed from 1 μg of nanofiber, and a bilayer sensor having a bilayer of compounds 2 / 3, each layer formed from 3 μg of nanofiber. [Figure 18B] FIG. 1 shows the sensor response to α-D-lactose at concentrations of 10 to 20 mg / m3 for a comparative sensor using only compound 2, a comparative sensor using only compound 4, a bilayer sensor having a bilayer of compounds 2 / 4, each layer formed from 1 μg of nanofiber, and a bilayer sensor having a bilayer of compounds 2 / 4, each layer formed from 3 μg of nanofiber. [Figure 18C] FIG. 1 shows the sensor response to α-D-lactose at concentrations of 10 to 20 mg / m3 for a comparative sensor using only compound 2, a comparative sensor using only compound 5, a bilayer sensor having a bilayer of compounds 2 / 5, each layer formed from 1 μg of nanofiber, and a bilayer sensor having a bilayer of compounds 2 / 5, each layer formed from 3 μg of nanofiber. [Figure 19A] FIG. 1 shows the sensor response to sodium bicarbonate at concentrations of 10 to 20 mg / m3 for a comparative sensor using only compound 2, a comparative sensor using only compound 3, a bilayer sensor having a bilayer of compounds 2 / 3, each layer formed from 1 μg of nanofiber, and a bilayer sensor having a bilayer of compounds 2 / 3, each layer formed from 3 μg of nanofiber. [Figure 19B]FIG. 1 shows the sensor response to sodium bicarbonate at concentrations of 10 to 20 mg / m3 for a comparative sensor using only compound 2, a comparative sensor using only compound 4, a bilayer sensor having a bilayer of compounds 2 / 4, each layer formed from 1 μg of nanofiber, and a bilayer sensor having a bilayer of compounds 2 / 4, each layer formed from 3 μg of nanofiber. [Figure 19C] FIG. 1 shows the sensor response to sodium bicarbonate at concentrations of 10 to 20 mg / m3 for a comparative sensor using only compound 2, a comparative sensor using only compound 5, a bilayer sensor having a bilayer of compound 2 / 5 with each layer formed from 1 μg of nanofiber, and a bilayer sensor having a bilayer of compound 2 / 5 with each layer formed from 3 μg of nanofiber.
[0010] The above attached drawings are presented to illustrate various aspects of the present invention, and the dimensions, materials, structures, configurations, and proportions shown in the drawings are not intended to be limiting of the scope of the present invention unless they are clearly stated in the claims. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] A number of specific embodiments are described below in sufficient detail to enable a person skilled in the art to carry out the present invention, but the present invention can be carried out in a form different from the embodiments, and can be carried out in a form with various modifications to the embodiments, and such other embodiments do not depart from the concept and scope of the present invention. Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the present invention described in the claims, but is intended for illustrative purposes only in describing the characteristics and properties of the present invention, and is not intended to be limiting, and is intended to provide a sufficient description that enables a person skilled in the art to carry out the present invention by describing the best mode for carrying out the present invention. Therefore, the scope of the present invention should be defined only by the claims.
[0012] definition In describing the invention in the specification and claims, the following phraseology and terminology will be used.
[0013] When singular or plural is not specified or is not clear from the context, it may mean either the singular or the plural. Thus, for example, if a reference is made to a "particle," it may mean either a single particle or multiple particles. Also, if a reference is made to a "treatment," it may mean either the treatment is performed once or multiple times.
[0014] The term "about" used in the description and claims means that there is a tolerance for the period, amount, numerical value, etc. to which it is attached. The tolerance can be easily determined by a person skilled in the art. However, unless otherwise specified, the tolerance expressed by the term "about" is generally 2% or less, and in many cases 1% or less, and in some cases 0.01% or less.
[0015] The term "substantially" as used in the specification and claims with respect to a particular attribute or condition means that deviation from the particular attribute or condition is sufficiently small that it is not readily measurable. The amount of deviation that is acceptable may, in some cases, depend on the particular circumstances.
[0016] The term "adjacent" as used in the specification and claims means that two structures or structural elements are in close proximity to one another. In particular, two components described as "adjacent" may abut one another or may be connected to one another. Moreover, such two components may be in close proximity to one another but not in contact with one another. The actual proximity may depend on the particular circumstances of the situation.
[0017] In the description and claims, for convenience, multiple item elements, multiple structural elements, multiple components, and / or multiple materials may be listed in the form of a list. In such cases, the individual elements or materials included in the same list are not related to each other, but are included in the list as independent elements or materials. Therefore, multiple elements or materials included in the same list should not be interpreted as being equivalent in nature just because they are listed together in the same list, but should be interpreted as being equivalent only if they are expressly stated to be equivalent.
[0018] The term "at least one of" used in the description and claims is synonymous with "one or some of." For example, "at least one of A, B, and C" clearly indicates that it may include only A, only B, only C, and any combination of two or more of them.
[0019] In the specification and claims, numerical data such as concentration, amount, etc. may be presented in the form of a range of values. The purpose of presenting such a range of values is to make it simple and clear, and the interpretation of the range of values must be flexible. In other words, not only the upper and lower limits of the range, which are the specified values, but also all the numerical values included in the range and all the subranges included in the range must be treated as specified. For example, a numerical range of about 1 to about 4.5 implies not only the limit values 1 and 4.5 specified therein, but also other numerical values such as 2, 3, and 4, and also subranges included in the range, such as 1 to 3, 2 to 4, etc. The same principle is also applied when only one numerical value is specified, and for example, the description "less than about 4.5" should be interpreted as implying all of the numerical values and numerical ranges exemplified above. Furthermore, such an interpretation should be applied regardless of the size of the numerical range and regardless of the characteristics represented by the numerical value.
[0020] When a claim describing a method or process invention includes multiple steps, the invention is not limited to the steps being performed in the order described in the claim, and the order of the steps may be changed. In addition, the limitation defined by the description "means for doing" and the description "step for doing" is limited by (a) the terms "means" or "step" being clearly stated, and (b) what is "done." With respect to the description "means for doing," the structure, materials, operations, etc. required to "do" it are as described in the specification. Therefore, the scope of the present invention is defined as the invention described in the claims and its legal equivalents, and is not defined by the detailed description of the specification, much less by the examples shown in the specification.
[0021] Sensor for detecting solid particles of target salt The technology described herein is a low-cost, low-power, compact sensor capable of determining at least one chemical component of a solid particle of a target salt by a solid-state ion-exchange process that releases one of the chemical compounds as a free, neutral molecule, which is then detected by a chemical sensor.
[0022] The particles to be detected are, for example, explosives or narcotics, and are particles in which an acid component and a base component are ionically bonded to form a salt. The ionic bond is dissociated by an ion exchange process by introducing a base or an acid. When a base is introduced, the base removes the acid component from the target salt, and the base component of the target salt is released in the form of a free base. When an acid is introduced, the acid removes the base component of the target salt, and the acid component of the target salt is released in the form of a free acid. The released components are detected. In some embodiments, the released components are detected using chemical sensors, mass spectroscopy, or other methods. This disclosure discusses the capture of airborne solid particles and the dissociation of the components using an ion exchange process, as well as a method for detecting target components with specificity and the use of the detection method for identifying exposure to ionic compounds such as fentanyl.
[0023] In the sensors described herein, the ion exchange process is carried out using an ion exchange medium made of a multiporous material functionalized with basic or acidic functional groups, which then displace the acid or base moiety of the target salt, thereby converting the target salt to a free base or free acid. The multiporous material may be any material that has a material structure that allows gas and the solid particles of the target salt contained therein to enter the pores of the material. According to some embodiments, the multiporous material may be made of organic nanofibers, polymer nanofibers, carbon nanotubes, silicon nanowires, metal oxide nanowires, boron nitride nanotubes, aerogels, xerogels, highly porous ceramics, metal organic frameworks (MOFs), glassy carbons, chalcopyrites, chalcogenides, or any combination thereof.
[0024] According to one embodiment, the ion exchange medium is an organic nanofiber functionalized with a base (e.g., primary amines). Once the salt particles are adsorbed onto the nanofiber, the strong basicity of the nanofibers causes the acid component (e.g., hydrochloric acid) to be released from the salt particles. The organic material and one-dimensional structure of the nanofibers provide an effective diffusion path for the acid component to diffuse quickly, and also provide a large effective surface area to drive the ion exchange process. In addition, the nanofibers form a thin, porous layer that aids in the transport of the released components. According to some embodiments, the particles to be detected are fentanyl hydrochloride, a common opioid, which undergoes an ion exchange process to release the free base fentanyl.
[0025] According to another embodiment, the sensor comprises two components: an upper adsorbent layer and a lower sensitive layer. The upper adsorbent layer captures the particles and allows the release of the target component by the ion exchange process described above. The lower sensitive layer allows the detection of the released salt target component, e.g., by a change in electrical conductivity. The sensitive layer comprises a second porous material functionalized to detect the released free base or free acid that migrates from the adsorbent layer. Any of the various porous materials listed above may be used as the sensitive layer material. According to one embodiment, the sensitive layer comprises an organic nanofiber functionalized to detect the free base or free acid of the target salt, e.g., fentanyl in free base form. The organic nanofiber is in contact with a pair of electrodes that apply a bias potential to the organic nanofiber. The nanofiber changes its electrical conductivity in response to the target chemical component, resulting in a measurable change in current. Chemical sensors of different configurations can also be used, including, for example, chemical sensors using electrochemical cells, conductive polymers, fluorescent polymers, colorimetric sensors, inorganic nanostructures, nanotubes (such as boron nitride nanotubes and carbon nanotubes), graphene, two-dimensional dichalcogenides, and metal oxides.
[0026] The dual-layer sensor of the above structure may be combined with various accessories to improve the ease of use of the sensor or to enhance the detection capabilities of the sensor into a single device. Such a device may include an interface between the sensor and the environment and / or an interface between the sensor and the user. According to some embodiments, such a device may include several components or subsystems, such as a housing, a sampling system (passive and active) that aids the interaction of the sensor with the environment, the sensor itself, electronic components for operating the sensor (e.g. amplifiers, A / D converters, multiplexers, microcontrollers, passive components, etc.), power supplies (e.g. batteries, transformers, etc.), firmware for operating the system, user interfaces (e.g. tactile alarms, visual alarms, audio alarms, displays, etc.), and communication devices (e.g. wi-fi, Bluetooth, USB, LTE, LoRa, etc.).
[0027] Moreover, such devices can be in various forms. One example of such a form is a wearable detector. According to one embodiment of this form, a dual-layer sensor is built into a battery-powered wearable device. The size of the wearable device is suitable for attachment to the body or clothing. For example, the length, width, and / or height of the wearable device may be about 0.5 inches to about 4 inches. The target salt particles may be actively pumped into the sensor, such as by using a blower. The presence of the target compound may be notified to the user by an audio, visual, or tactile alarm. One example of such a device is a wearable sensor capable of detecting fentanyl compounds that should be equipped by organizations with first responders. An example of such a wearable sensor is described in U.S. Patent Application Publication No. 2020 / 0326286, the disclosure of which is incorporated herein by reference. Furthermore, such wearable devices are not limited to the sensors described in the US publication.
[0028] In another embodiment of the sensor, the sensor may be a fixed-mount device. An example of such a device is a device similar to a smoke detector. Such a device is mounted at a fixed mounting location (e.g., on a wall). The sensor in the device is open to the environment and passively samples. The power source may be a battery or may be powered from an electrical wiring. One example of such a device is a smoke detector with a sensor capable of discriminating between smoke and steam. Another example is an outdoor air monitor with a sensor capable of discriminating between a first particulate matter (e.g., soot, dust, etc.) and a second particulate matter (e.g., ammonium nitrate, etc.).
[0029] The sensitive layer is a layer formed by coating a chemiresistive sensing material on or between a pair of electrodes. In various embodiments described herein, the material of the sensitive layer is electrically connected to the pair of electrodes, so that a current can be passed from one electrode to the other through the sensitive layer. The chemiresistive sensing material changes its resistivity by exchanging electrons with a gas adsorbed on the chemiresistive sensing material. By electronically measuring this change in resistivity, a fingerprint profile corresponding to a particular gas can be generated. As described above, when the target compound is fentanyl, the fentanyl is present in the form of solid powder particles rather than gas. That is, fentanyl is often present in the form of fentanyl hydrochloride powder, and the vapor pressure of fentanyl hydrochloride is negligibly small. In fact, the concentration of fentanyl in the saturated vapor of fentanyl hydrochloride is much lower than the dangerous concentration of fentanyl. The risk of inhaling fentanyl is nothing other than the risk of inhaling solid particles of fentanyl hydrochloride. Thus, the dual layer sensor described herein is constructed such that the top adsorbent layer adsorbs solid particles of fentanyl hydrochloride, and the free base form of fentanyl diffuses into the sensitive layer, where it is detected by a change in resistivity of the sensitive layer. Since fentanyl is a weak base, a strong base can be used to remove the hydrochloric acid from the fentanyl hydrochloride, thereby converting it to the more volatile free base form of fentanyl. The sensitive layer of the sensor described herein detects this free base form of fentanyl. Fentanyl has a pKa value of 8.4, whereas primary and secondary alkyl amines have a higher pKa value of 10.5. Therefore, a primary or secondary alkylamine may be used in the fabrication of a sensor, which can easily dissociate fentanyl hydrochloride and convert it to the free base form of fentanyl.
[0030] Although fentanyl hydrochloride has been described as an example, the sensor described herein can be used to detect various other target salts. If the target salt is a salt that can be identified by converting the characteristic base component of the target salt into a free base form, the sensor's adsorption layer can be functionalized with a basic functional group to eliminate the acid component of the target salt, and the free molecule of the base component can be detected in the sensitive layer. On the other hand, if the target salt is a salt that can be identified by converting the characteristic acid component of the target salt into a free acid form, the sensor's adsorption layer can be functionalized with an acid functional group to eliminate the base component of the target salt, and the free acid can be detected in the sensitive layer.
[0031] The bilayer sensor described herein is capable of detecting target compounds at low concentrations within a reasonable response time. In experimental testing, a sensor configured to detect fentanyl hydrochloride was tested with a fentanyl hydrochloride simulant at a concentration of 1.6 mg / m 3 The sensor was able to detect 100 mg / m2 of a fentanyl hydrochloride simulant within five minutes. The same sensor was also exposed to chain breakers, such as mannitol, lactose, and baking soda, at concentrations of 10–20 mg / m2. 3 No sensor response was observed even at a high concentration of 1.5g / mL. Exposure to another interfering substance, metamizole, elicited a small sensor response, but the direction of the sensor response was opposite to that of the sensor response to the fentanyl hydrochloride simulant.
[0032] These test results demonstrate that the sensors described herein are capable of detecting fentanyl in its natural form and at its natural concentrations, and are suitable for incorporation into a small, wearable device that can rapidly alert first responders to exposure to fentanyl, facilitating diagnosis of the exposure, and ultimately improving the survival rate of first responders exposed to fentanyl.
[0033] According to some embodiments, the porous material of the adsorption layer and / or the porous material of the sensing layer are made of organic nanofibers. According to some embodiments, the organic nanofibers are formed by assembling building block molecules that are functionalized to change their sensitivity and selectivity to the compounds to be detected. Once the building block molecules are assembled to form the nanofibers, the nanofibers are coated on a pair of electrodes to form a layer. In this way, the change in resistivity of the nanofiber layer due to the interaction between the nanofibers and molecules in the environment can be measured. The change in resistivity of the nanofibers is due to the electron density change caused by molecules in the environment adsorbing on the surface of the nanofibers and transferring electrons. Since the sensor response is not due to covalent bonds, the sensor can recover from the effect of the interaction, and therefore the sensor can be reused. The magnitude of the sensor response is proportional to the Langmuir adsorption model, and the detected chemical can be quantified based on the magnitude of the sensor response. Specific examples of building block materials for forming nanofibers include, but are not limited to, those listed in U.S. Pat. Nos. 8,486,708, 8,889,420, 8,703,500, 8,809,063, U.S. Patent Application Publication No. US 2014 / 0235493 A1, U.S. Patent Application Publication No. US 2018 / 0201612 A1, and U.S. Patent Application Publication No. US 2017 / 0160252 A1, the disclosures of which are incorporated herein by reference. Such materials can be functionalized with amines as described herein to form basic nanofibers for the adsorption layer, and can be used to form nanofibers for the sensitive layer, as described herein.
[0034] FIG. 1 is a cross-sectional side view of an embodiment of a sensor 100 according to the present disclosure. This embodiment includes a support substrate 110, a pair of electrodes 120 formed on the support substrate, a sensitive layer 130 formed on the support substrate and the electrodes, and an adsorbent layer 140 formed on the sensitive layer. The sensitive layer is connected to the pair of electrodes, which are separated from each other by the sensitive layer, thereby forming a current path for passing a current from one electrode through the sensitive layer to the other electrode. Therefore, a change in the electrical conductivity of the sensitive layer can be measured by passing a current between the pair of electrodes. The adsorbent layer comprises an ion exchange medium formed of a first porous material. The first porous material is functionalized with basic or acidic functional groups to remove an acid or base component from the target salt to generate a free base or free acid of the target salt. The sensitive layer comprises a second porous material. The second porous material is functionalized to detect the free base or free acid of the target salt by a change in electrical conductivity.
[0035] The specific sensor structure shown in FIG. 1 is an example. The arrangement of the components of the sensor may be different from that of this example. For example, the sensitive layer in FIG. 1 is formed on the upper surface of the electrodes and fills the space between the two electrodes. In contrast, in some other examples, the material forming the sensitive layer is not located on the upper surface of the electrodes, and in some other examples, the material forming the sensitive layer does not fill the space between the two electrodes. Any arrangement may be used as long as the material forming the sensitive layer is electrically connected to both of the pair of electrodes and can pass a current from one electrode through the sensitive layer to the other electrode. Furthermore, in some examples, the adsorption layer covers the entire sensitive layer, and in other examples, the adsorption layer covers only a part of the sensitive layer. In some examples, the adsorption layer is formed on the electrodes, and in other examples, the adsorption layer is not formed on the electrodes. In some examples, both the adsorption layer and the sensitive layer are formed between the two electrodes. Also, in some embodiments, the adsorption layer and the electrode are not directly connected because they are separated by a sensitive layer. In some such embodiments, the current flowing from one electrode to the other only flows through the sensitive layer and not through the adsorption layer. In other embodiments, the current flowing from one electrode to the other flows through the adsorption layer in addition to the sensitive layer.
[0036] 2A-2D are diagrams showing the manufacturing process of a sensor 200 according to another embodiment. FIG. 2A shows a top view of a support substrate 210 and two electrodes 220 formed on the support substrate. FIG. 2B shows a sensitive layer 230 formed on the support substrate and the electrodes, the sensitive layer being made of nanofibers 232. FIG. 2C shows an adsorption layer 240 formed on the sensitive layer, the adsorption layer being made of nanofibers 242. FIG. 2D shows a cross-sectional side view of the sensor. As mentioned above, the nanofibers of the adsorption layer are functionalized with basic functional groups to remove acidic components from the target salt. The nanofibers of the sensitive layer are adapted to detect the free base form of the target salt by a change in electrical conductivity.
[0037] In one embodiment, a sensor of the configuration shown in Figures 2A-2D is used to detect fentanyl hydrochloride. The adsorbent layer captures fentanyl hydrochloride particles and converts the fentanyl hydrochloride to the free base form of fentanyl by removing hydrochloric acid from the fentanyl hydrochloride. The free base form of fentanyl diffuses into the sensitive layer where it is detected. The adsorbent layer in this configuration has sufficient density to capture the fentanyl hydrochloride particles and provides sufficient interfacial interactions to completely convert the fentanyl hydrochloride particles to the free base form of fentanyl. The nanofibers in the sensitive layer allow for high sensitivity detection of the free base form of fentanyl.
[0038] Another embodiment of the sensor 300 is shown in Figs. 3A-3B. The sensor includes a pair of electrodes 320 that constitute an interdigital electrode. The electrodes are formed of a metal layer patterned on a support substrate 310. Fig. 3A shows the support substrate and the electrodes without the layers covering them so that they can be seen clearly. Fig. 3B is a cross-sectional side view of the sensor, showing a sensitive layer 330 and an adsorption layer 340 formed on the support substrate and the electrodes. In this embodiment, each of the two electrodes includes an electrode body and a finger portion extending from the electrode body toward the other electrode. In this embodiment, the finger portion of the electrode is narrower than the electrode body. However, in another embodiment, the electrode body and the finger portion may be the same thickness, and the entire electrode may be formed with a constant thickness. By using an interdigital electrode, the current flowing between both electrodes through the sensitive layer when the target molecules move into the sensitive layer by diffusion can be made large, thereby increasing the sensitivity of the sensor.
[0039] 4A, 4C, and 4E are schematic diagrams showing the detection process of fentanyl hydrochloride using sensor 400, and 4B, 4D, and 4F are theoretical sensor responses that may occur during the process. In FIG. 4A, fentanyl hydrochloride particles 402 enter the sensor. In FIG. 4C, fentanyl hydrochloride particles are adsorbed to the adsorption layer 440. If there is charge transfer between the nanofibers in the adsorption layer and the particles, a small sensor response may occur. In FIG. 4F, an ion exchange reaction occurs, i.e., the nanofibers functionalized with basic functional groups convert fentanyl hydrochloride into the free base form of fentanyl and release it, and the released fentanyl molecules migrate into the sensitive layer 430. The nanofibers in the sensitive layer and the fentanyl molecules interact with each other through charge transfer, increasing the signal output of the sensor response. The above detection scheme allows for the detection of particles of non-volatile substances such as fentanyl suspended in the air.
[0040] Another embodiment of the sensor 500 shown in Fig. 5 includes a support substrate 510, a pair of electrodes 520, a sensitive layer 530, and an adsorption layer 540, similar to the above-described embodiment. In addition, the sensor includes a housing 550 that encloses the support substrate, the electrodes, the sensitive layer, and the adsorption layer. The sensor also includes a blower 460 for blowing air into the housing and onto the adsorption layer, thereby attracting target salt particles in the surrounding environment. The sensor further includes an alarm means 570 connected to the electrodes and configured to generate an alarm signal. The alarm signal can be a tactile signal, a visual signal, an audio signal, a display, or a combination thereof.
[0041] More specifically, the target salts may be designed to detect a variety of target salts. The target salts include a base and an acid component. In various embodiments, the target salt may be a hydrochloride, sodium salt, sulfate salt, acetate salt, phosphate salt, diphosphate salt, chloride salt, potassium salt, maleate salt, calcium salt, citrate salt, mesylate salt, nitrate salt, tartrate salt, aluminum salt, gluconate salt, or perchlorate salt, or may be other salts including acids and bases. In some embodiments, the target salt is an alkaloid salt. In particular, the target salt is an opiate salt. In particular, the target salt is fentanyl hydrochloride or carfentanil. The target salt is in the form of solid particles. In some embodiments, the target salt has an average particle size of about 0.1 μm to about 10 μm. According to some other embodiments, the target salt has an average particle size of about 0.1 μm to about 5 μm, or about 0.1 μm to about 1 μm, or about 1 μm to about 5 μm, or about 1 μm to about 10 μm. Note that the term average particle size as used in the present disclosure refers to the average value of the longest dimension of the particles if the particles are non-spherical, and refers to the average value of the diameter of the particles if the particles are spherical.
[0042] Various rigid materials can be used as the material of the support substrate for fabricating the sensor. According to some embodiments, the support substrate is made of glass, silicon, alumina, sapphire, mica, quartz, plastic, or some combination thereof. The support substrate can also be a flexible substrate. Suitable examples of flexible substrates include, but are not limited to, substrates made of polyethylene and substrates made of MYLAR (trademark). There are no particular limitations on the thickness or dimensions of the support substrate. In some embodiments, the thickness of the support substrate is about 0.1 mm to about 1 cm, and in some embodiments, the thickness is about 0.1 mm to about 2 mm.
[0043] As mentioned above, the sensor comprises two layers of porous materials. In many embodiments, the two layers are made of different porous materials, i.e., the upper adsorption layer is made of a first porous material and the lower sensing layer is made of a second porous material. The first porous material and / or the second porous material can be organic nanofibers, polymer nanofibers, carbon nanotubes, silicon nanowires, metal oxide nanowires, boron nitride (NB) nanotubes, aerogels, xerogels, highly porous ceramics, metal organic frameworks (MOFs), glassy carbons, chalcopyrites, chalcogenides, or some combination thereof. Furthermore, the porous materials are functionalized with various functional groups. According to some embodiments, the first porous material is functionalized with a basic functional group to generate a free base of the target salt when the target salt particles are adsorbed on the first porous material. According to some such embodiments, the second porous material is made of an acidic nanofiber functionalized to detect the free base of the target salt. Examples of the basic functional group include primary amino groups, secondary amino groups, tertiary amino groups, and combinations thereof. According to some embodiments, the basic functional group is hexylamine, ethylethylamine, dimethylbutylamine, or combinations thereof. According to some embodiments, the first porous material is made of organic nanofibers with such functional groups.
[0044] In some other embodiments, the first porous material is functionalized with an acidic functional group to generate a free acid of the target salt when the target salt particles are adsorbed onto the first porous material. Specific examples of the acidic functional group include, for example, carboxylic acids, phenols, thiophenols, alkylphosphonic acids, aromatic phosphonic acids, alkylphosphorothioic acids, etc. As a general guideline, organic compounds having a pKa of 7.0 or less are used as the acidic functional group.
[0045] According to some embodiments, the first porous material is made of organic nanofibers. According to some embodiments, the first porous material is made of a first organic nanofiber, which is made of a laminated molecule formed by assembling and stacking molecules, the laminated molecules being selected from the group consisting of 3,4,9,10-perylene-tetracarboxylic diimide, 3,4,9,10-perylene-tetracarboxylic dianhydride, perylene-3,4,9,10-tetracarboxylic-3,4-anhydride-9,10-imide, indolocarbazole derivatives, and oligomers composed of 3 to 9 carbazole derivative monomers, and at least a part of the laminated molecule is functionalized with a basic functional group. According to some embodiments, the first organic nanofiber is made of a laminated molecule formed by assembling and stacking molecules having any one of the 12 molecular structures shown in the following chemical formulas I to XII.
[0046] [ka] (I)
[0047] [ka] (II)
[0048] [ka] (III)
[0049] [ka] (IV)
[0050] [ka] (V)
[0051] [ka] (VI)
[0052] [ka] (VII)
[0053] [ka] (VIII)
[0054] [ka] (IX)
[0055] [ka] (X)
[0056] [ka] (XI)
[0057] [ka] (XII)
[0058] The thickness of the adsorption layer may be sufficient to capture particles of the target salt and to allow the base component or acid component of the captured target salt to diffuse into the sensitive layer. According to some embodiments, the thickness of the adsorption layer is about 50 nm to about 5 μm. According to some other embodiments, the thickness of the adsorption layer is about 50 nm to about 1 μm, or about 50 nm to about 500 nm, or about 1 μm to about 5 μm. According to some other embodiments, the mass per area of the adsorption layer is 3 mm 2 According to some embodiments, the area of the adsorption layer is about 0.1 mm 2 ~10 mm 2 , or about 0.1 mm 2 ~1 mm 2, or about 1 mm 2 ~10 mm 2 According to some embodiments, the pore size of the adsorption layer is from about 10 nm to about 1 μm, or from about 10 nm to about 500 nm, or from about 10 nm to about 100 nm.
[0059] According to some further embodiments, the sensitive layer is made of a second porous material. According to some embodiments, the second porous material is made of a second organic nanofiber, which is made of a laminated molecule formed by assembling and stacking molecules, and the laminated molecule is selected from the group consisting of substituted or unsubstituted 3,4,9,10-perylene-tetracarboxylic diimide, substituted or unsubstituted 3,4,9,10-perylene-tetracarboxylic dianhydride, substituted or unsubstituted perylene-3,4,9,10-tetracarboxylic-3,4-anhydride-9,10-imide, indolocarbazole derivatives, and oligomers formed of 3 to 9 carbazole derivative monomers. According to some further embodiments, the second porous material is made of a second organic nanofiber, which is made of a laminated molecule formed by assembling and stacking molecules having one of the two molecular structures shown in the following chemical formulas XIII and XIV.
[0060] [ka] (XIII)
[0061] [ka] (XIV)
[0062] According to some embodiments, the thickness of the sensitive layer is about 50 nm to about μm, or about 50 nm to about 1 μm, or about 1 μm to about 5 μm. Also, according to some embodiments, the mass per area of the sensitive layer is less than 3 mm 2 Approximately 0.1 μg to approximately 6 μg per serving.
[0063] To form the pair of electrodes of the sensor, for example, a conductive material may be deposited on a support substrate to form two electrodes separated from each other by a gap. As described above, the sensitive layer extends across the gap, so that a current can flow from one electrode through the sensitive layer to the other electrode. According to some embodiments, the material for forming the pair of electrodes is gold, titanium, indium tin oxide, indium zinc oxide, tungsten, aluminum, platinum, silver, copper, PEDOT:PSS, or a combination of some of these. There is no particular restriction on the thickness of the electrodes. In some embodiments, the thickness of the electrodes formed by deposition is about 5 nm to about 100 μm. In some embodiments, the gap width of the gap separating the pair of electrodes is about 50 nm to about 100 μm.
[0064] Working Example Three novel molecules used to form the nanofibers in the adsorption layer of the bilayer sensor were synthesized and their molecular structures were characterized by nuclear magnetic resonance spectroscopy. Nanofibers were grown by injecting a concentrated solution of each molecule into a non-solvent, which caused the molecules to aggregate. Because each molecule had a planar π-conjugated structure, growth proceeded primarily in one direction, resulting in the formation of the nanofibers. After confirming that the nanofibers were in the correct molecular assembly state, they were deposited on an electrode to form a layer of the nanofiber, which was then imaged by scanning electron microscopy (SEM) and the electrical properties of the layer were measured to characterize each nanofiber.
[0065] The fabrication of the bilayer sensor can be carried out using any suitable fabrication technique. For example, the sensitive or adsorbent layer can be formed by coating the electrodes with a suspension of nanofibers. The coating layer must provide sufficient coverage (i.e., the lower layer must be able to fill the gap between the electrodes, and the upper layer must be able to cover the entire area of the lower layer and achieve the desired layer thickness). If the layer is too thick, depending on the density and porosity of the nanofiber network from which the layer is formed, the diffusion time may be long, resulting in a long sensor response time or reduced sensor sensitivity.
[0066] Fentanyl can be detected by using a sensor that responds to fentanyl hydrochloride particles in the environment. A Blaustein Atomizer (BLAM) can also be used to convert a solution into aerosol particles with a particle size of 0.7 μm to 2.5 μm that can be inhaled. The mist generated by converting the solution into aerosol particles is introduced into a dissipative dryer to dissipate the solvent, and dry particles are obtained at the outlet of the dissipative dryer. The concentration of the aerosol can be controlled by changing the injection rate of the solution injected into the BLAM, or by diluting the aerosol sample with air.
[0067] Fentanyl simulant particles were generated from a fentanyl simulant solution. The particles of the fentanyl simulant in the form of hydrochloride salt generated using the particle generator were quantified prior to testing. The quantification was performed using a "DUSTTRAK II" particle counter manufactured by TSI Inc. (USA) (DUSTTRAK is a trademark). In the fentanyl simulant test, the fentanyl simulant was set at three different concentrations to investigate whether the sensor response had dose dependency. The three concentrations were 1 to 2 mg / m 3 , 2-4 mg / m 3 , and 8 to 16 mg / m 3 It was.
[0068] In environments where fentanyl is present, chain breakers are often present as well, and these chain breakers can interfere with the sensor. Using the same test equipment as used to test fentanyl simulants, we tested several interfering substances to determine their potential cross-reactivity. The substances tested were metamizole, mannitol, lactose, and baking soda, and the test concentrations of these substances were 10 times higher than the test concentrations of the fentanyl simulants.
[0069] The newly synthesized nanofibers for use as the adsorption layer nanofibers each had a unique structure and exhibited various properties. The molecular formulas of the new nanofiber molecules and scanning electron microscope (SEM) images of the adsorption layers formed with the new nanofibers are shown in Figures 6A-6D. Surface area, porosity, and functional group activity are all factors to consider when selecting a nanofiber for the detection of a particular target compound. By varying the values of these factors, the binding sensitivity and selectivity can be increased or decreased, and therefore tailored for the detection of a particular target compound. Figure 6A shows a nanofiber of bis(N-hexylamine). Figure 6B shows a nanofiber of bis(N-ethylethylamine). Figure 6C shows a nanofiber of bis(N-propylpropylamine). Figure 6D shows a nanofiber of bis(dimethylbutylamine), which has an intermediate structure between the nanofibers of Figures 6A and 6B. FIG. 7A shows the sensitive layer formed by coating on an electrode according to one embodiment, and FIG. 7B shows the sensitive layer that was coated a second time using ethanol without nanofibers to produce a comparative sensor.
[0070] Furthermore, a bilayer sensor was fabricated using nanofibers to form the sensitive layer and nanofibers to form the adsorption layer. The standard amount of nanofibers used to form the layers was 6 μg for both the sensitive layer and the adsorption layer. Prior to fabrication of the bilayer sensor, the current through each layer was measured, and the current through the sensitive layer was 1.1 nA, and the current through the adsorption layer was 130 μA. When the current through the bilayer sensor was measured after the fabrication was completed, it was 180 nA, which was two orders of magnitude higher than the current through the sensitive layer measured previously. This increase in current is believed to be due to the increase in the electron density of the sensitive layer caused by doping from the adsorption layer to the sensitive layer, which in turn increased the overall conductivity of the bilayer sensor. Another possible reason for this increase may be that most of the current through the sensor passed through the adsorption layer, because the adsorption layer has a higher conductivity than the sensitive layer. However, this second reason is unlikely to be valid, since charge is less likely to move perpendicular to the electrode surface. Too much doping of the sensitive layer could reduce the sensitivity of the bilayer sensor to fentanyl, so the amount of nanofiber forming the adsorption layer was reduced to reduce the change in sensor current. Reducing the thickness of the adsorption layer also has the effect of facilitating the transport of free base fentanyl into the sensitive layer, a process that is likely to be upper-bounded by diffusion.
[0071] We fabricated multiple bilayer sensors with uniform structures. Among these bilayer sensors, the adsorption layer was formed from 1 μg of bis-N,N-dimethylbutylamine nanofibers and the nanofibers were formed from 3 μg of bis-N,N-dimethylbutylamine nanofibers. The nanofibers forming the sensitive layer were all three types of nanofibers. Figures 8A to 8D show SEM images of the bilayer sensors. Figure 8C shows an image of a bilayer sensor sample with an adsorption layer formed from 1 μg of nanofibers, where the sensitive layer is clearly visible near the top edge of the image. In addition, the nanofibers of the sensitive layer are visible through the voids in the adsorption layer at some other positions in the image. In the bilayer sensor sample with an adsorption layer formed from 3 μg of nanofibers (Figure 8D), the sensitive layer is difficult to see, although the sensitive layer can be seen in some places near the corners of the image, which indicates that the adsorption layer is not thick enough to completely cover the sensitive layer. When the amount of nanofibers forming the adsorption layer was either 1 μg or 3 μg, the adsorption layer was formed as a uniform thin film, and the sensitive layer below the adsorption layer was exposed.
[0072] Furthermore, a bilayer sensor sample was prepared in which the sensitive layer was formed of nanofibers of compound 1 and an adsorption layer was formed of 1 μg of nanofibers of bis-butylamine on the sensitive layer (1 μg sample: FIG. 9A), and a bilayer sensor sample was prepared in which the adsorption layer was formed of 3 μg of nanofibers of bis-butylamine on the sensitive layer (3 μg sample: FIG. 9B). Figure 9C shows the sensitive layer before the adsorption layer was formed on it. In the 1 μg sample, the sensitive layer is almost covered by the adsorption layer, but the sensitive layer below the adsorption layer is slightly visible. In the 3 μg sample, which uses a larger amount of nanofibers to form the adsorption layer, the sensitive layer is completely covered by the adsorption layer. However, even if the sensitive layer is completely covered, there is no problem as long as the adsorption layer is not too thick, because the adsorption layer is porous and therefore efficiently moves the free base form of fentanyl by diffusion.
[0073] Figures 10A and 10B show a bilayer sensor sample (1 μg sample: Figure 10A) in which an adsorption layer was formed on the sensitive layer with 1 μg of bis(N-ethylethylamine) nanofibers, and a bilayer sensor sample (3 μg sample: Figure 10B) in which an adsorption layer was formed on the sensitive layer with 3 μg of bis(N-ethylethylamine) nanofibers. The area surrounded by a red oval shows the sensitive layer underneath. Figure 10C shows the entire sensitive layer before the adsorption layer was formed on top. The bis(N-ethylethylamine) nanofibers are thick, so the adsorption area for fentanyl particles is small, but on the other hand, the route of fentanyl movement to the sensitive layer by diffusion may be more efficient. In the bilayer sensor sample of the 3μg sample, the sensitive layer under the adsorbent layer is not easily visible, but the adsorbent layer formed by the bis(N-ethylethylamine) nanofibers has a high porosity, so the diffusion transport is expected to be good. The inability to see the sensitive layer may also be due to the narrow depth of field of the SEM. The nanofibers of bis(N-ethylethylamine) formed an adsorbent layer with a lower packing density than the nanofibers of other materials, but it seems that the same amount of nanofibers can form a thicker adsorbent layer.
[0074] FIG. 11 shows the chemical structural formulas of the molecules of the sensitive layer nanofibers and adsorption layer nanofibers selected for testing, as well as the compound names of those molecules (Compound 1 to Compound 5) used in this disclosure.
[0075] A selection of fentanyl simulants that would generate a sensor response similar to that for fentanyl was performed. Simulants had to be used in the initial tests, partly for safety reasons and partly because a permit was required for the use of fentanyl. First, four substances with molecular structures similar to fentanyl were selected as candidates. These candidates are shown in Figure 12. The four substances that are candidates for fentanyl simulants are norfentanyl hydrochloride (2 in Figure 12), propenamido-2-methyl-N-[1-(phenylmethyl)-4-piperidinyl] (3 in Figure 12), propenamido-N-[1-[2-(4-hydroxyphenyl)methyl]-4-piperidinyl]-N-phenyl (4 in Figure 12), and benzylfentanyl (5 in Figure 12). Finally, we decided to use substance 3 in Figure 12 as a fentanyl simulant. This is because substance 4 in Figure 12 has a phenol group that may be detected by nanofibers, and it was found that substances 2 in Figure 12 are controlled drugs.
[0076] Fentanyl simulants were tested at three concentrations (1–2 mg / m 3 , 2-4 mg / m 3 , and 8 to 16 mg / m 3 In addition, tests for three interfering substances (D-mannitol, metamizole, and α-D-lactose) were also performed.
[0077] Figures 13A to 13C show the sensor responses obtained by various experiments. In the experiments, only the solvent was injected first. The first black arrow (black arrow on the left) indicates the zero point of the baseline, at which the valve was opened to start supplying the analyte sample solution from the sample injection syringe pump. Since it takes time for the injected analyte sample solution to reach the atomizer, the predicted time required for the analyte particles to reach the nanofiber was calculated based on the supply flow rate of the syringe pump. This predicted time is shown by the gray band in the figure. The second black arrow (black arrow on the right) indicates the time when the syringe pump was turned off and the valve was closed to stop the inflow of the analyte sample solution to the atomizer.
[0078] The sensor responses shown in Figures 13A to 13C include the sensor responses of the bilayer sensor with a bilayer consisting of a sensitive layer of compound 2 (i.e., a sensitive layer formed of nanofibers of compound 2) and an adsorption layer of compound 4 (i.e., an adsorption layer formed of nanofibers of compound 4) to the three concentrations of fentanyl simulants mentioned above. The first thing to notice is that the sensor with the adsorption layer of compound 4 has a dose-dependent sensor response, which is clearly shown in Figures 13B and 13C. In the test with the lowest concentration of fentanyl simulant (Figure 13A), little to no sensor response occurs. The amine functional group at the end of the alkyl chain of compound 4 has the highest sensor response to free base molecules compared to the other functional groups of the adsorption layer, because the amine functional group is the functional group with the greatest ability to drive an ion exchange reaction with fentanyl hydrochloride particles and is the functional group that can generate a sensor response to fentanyl in the free base form.
[0079] The bilayer sensor with a bilayer consisting of a sensitive layer of compound 2 and an adsorbed layer of compound 4 (compound 2 / 4 bilayer sensor) showed a dose-dependence of the sensor response such that the higher the concentration of the fentanyl simulant, the higher the response output. As shown in FIG. 13C, the performance of the bilayer sensor with this configuration was better than that of the comparative sensor. The bilayer sensor with the adsorbed layer of compound 4 showed the largest difference from the comparative sensor with a sensitive adsorbed layer of compound 2 in the highest concentration test (FIG. 13C), and the difference was less significant in the two lower concentration tests (FIGS. 13A and 13B).
[0080] Figure 14A shows the sensor response of a bilayer sensor (compound 2 / 3 bilayer sensor) with a bilayer consisting of a sensitive layer of compound 2 and an adsorption layer of compound 3. Figure 14B shows the sensor response of a bilayer sensor (compound 2 / 4 bilayer sensor) with a bilayer consisting of a sensitive layer of compound 2 and an adsorption layer of compound 4. Figure 14C shows the sensor response of a bilayer sensor (compound 2 / 5 bilayer sensor) with a bilayer consisting of a sensitive layer of compound 2 and an adsorption layer of compound 5.
[0081] The sensor response to four substances that could potentially interfere with the sensor (D-mannitol, metamizole, sodium bicarbonate, and α-D-lactose) was examined at concentrations of 10–20 mg / m 3 The experiment was carried out with a setting of 0.01%. This concentration is about 10 times higher than the lowest set concentration of fentanyl simulants in the sensor response test for fentanyl simulants. The sensor response test for these four interfering substances was carried out because these interfering substances are chain breakers that are widely used in the final manufacturing process of fentanyl-based opioids that are actually distributed. The molecular structures of these four interfering substances are shown in Figure 15.
[0082] 16A to 16C show the results of the compound 2 / 3 sensor, the compound 2 / 4 bilayer sensor, and the compound 2 / 5 bilayer sensor at concentrations of 10 to 20 mg / m 316A shows the sensor response to metamizole. The sensor response to metamizole is a decrease in the output response, which is likely due to the sulfate pair in the metamizole chemical structure, and is quite different from the increase in the output response to the fentanyl simulant. FIG. 16A shows the sensor response of the compound 2 / 3 bilayer sensor and the two comparative sensors, both of which produce small responses. The bilayer sensor with 3 μg nanofibers in each layer produces a larger sensor response than the bilayer sensor with 1 μg nanofibers in each layer.
[0083] As shown in Figure 16B, the double-layered sensor of compound 2 / 4 also produced a sensor response to metamizole, while the two comparative sensors with a single layer of sensitive adsorption layer produced negligible sensor responses to metamizole. The comparative sensor with a sensitive adsorption layer formed of nanofibers of compound 4 produced a dose-dependent sensor response to fentanyl simulants, but did not produce a sensor response to metamizole, so this comparative sensor appears to have selectivity in favor of fentanyl simulants and may suppress the occurrence of false positives due to metamizole.
[0084] As shown in Figure 16C, the bilayer sensor of compound 2 / 5 generates a small response to metamizole compared to other bilayer sensors fabricated on the sensor card. This result indicates that the adsorption layer plays a major role in the sensor response. The adsorption layer of compound 5 generates a large sensor response to fentanyl simulants because the adsorption layer has amines that are easily accessible to the fentanyl simulants. In addition, the sensor response to interfering substances can be larger with a thicker adsorption layer than with a thinner adsorption layer. This is because the kinetics of the ion exchange reaction is determined by the accessibility and availability of the amines in the adsorption layer, and the sensor response is governed by the kinetics. In addition, the selectivity of the sensor can be improved by tuning the sensitive layer.
[0085] Furthermore, the response to metamizole was negligibly small even in the comparative sensor in which the sensitive adsorption layer was formed of the nanofiber of compound 2. Therefore, the nanofiber of compound 2 is also considered to be a suitable nanofiber for obtaining high selectivity. This test result suggests that the adsorption layer affects the selectivity. There is a potential possibility that the selectivity can be further increased by making the adsorption layer more suitable. In addition, by using a sensor array, it is possible to eliminate the possibility that the sensor response to metamizole interferes with the detection of fentanyl. For example, there is a concern that the sensor response to fentanyl and the sensor response to metamizole will cancel each other out, resulting in a zero response. Indeed, for a certain sensor, there is a ratio of fentanyl to metamizole that establishes such a canceling effect, but the ratio varies for each of the multiple sensors included in the sensor array. Therefore, by performing signal processing on the response signals of each of the multiple sensors, a selectivity that can overcome metamizole can be ensured.
[0086] Figures 17A-17C show the results of the measurements of the concentration of 10-12 mg / m 317A-17C , the sensor response to D-mannitol. D-mannitol does not have a functional group that interacts with the sensors. The sensor response of each of the two bilayer sensors shown in Figures 17A-17C is likely due to drift, and the bilayer sensors do not generate large sensor responses to the analyte. Therefore, it is unlikely that D-mannitol is an interfering substance for the bilayer sensors.
[0087] 18A to 18C show the concentrations of 10 to 20 mg / m 3 The results show that the bilayer sensor has the selectivity to selectively react with fentanyl, and therefore it can detect fentanyl even in the presence of other compounds such as α-D-lactose. The functional groups on the α-D-lactose molecule are similar to those on the D-mannitol molecule, and do not induce any reaction in the nanofiber. Therefore, α-D-lactose is unlikely to be an interfering substance. The test results indicate that the bilayer sensor has the selectivity to selectively react with fentanyl, and therefore it can detect fentanyl even in the presence of other compounds such as α-D-lactose.
[0088] The final interfering substance tested was sodium bicarbonate (baking soda). The sensor response to sodium bicarbonate is shown in Figures 19A-19C. The bilayer sensor and comparative sensor shown in Figures 19A-19C did not generate a sensor response to sodium bicarbonate because sodium bicarbonate does not have reactive sites to react with the nanofibers, and therefore sodium bicarbonate is unlikely to mask the presence of fentanyl under real-world conditions. Note that testing of mixtures of substances requires additional particle generators, test methodology, and sufficient test time.
[0089] The above-mentioned sensor is the only sensor based on a chemiresistive sensing technology that can provide a high degree of selectivity. Since the above-mentioned nanofibers are produced by utilizing the self-assembly of organic molecules, the structure of the nanofibers can be deliberately determined prior to production so that they respond to a specific analyte or group of analytes. Furthermore, the thin-film adsorption layer formed by the above-mentioned nanofibers has a large surface area and a high porosity, allowing adsorption and desorption to proceed at high speeds, and therefore, the detection limit of some chemicals can be reduced to the ppt level. Furthermore, since the above-mentioned nanofibers can function at room temperature and atmospheric pressure, they do not require a power source as in the case of techniques involving heating or decompression. The above-mentioned nanofibers further improve various drawbacks associated with optical techniques, particularly those related to lowering the detection limit and providing chemical specificity. Furthermore, by incorporating organic nanofibers, a low-cost, highly portable device can be constructed, and the device can be made to be a device that is significantly comparable in sensitivity and selectivity to laboratory devices.
[0090] List of other examples The following list describes specific examples of the techniques described herein. The specific examples are numbered for convenience. Examples 1 to 28 are sensors according to the techniques described herein. Examples 29 to 58 are methods for detecting solid particles of a target salt.
[0091] Example 1: A sensor for detecting solid particles of a target salt, comprising: a support substrate; an adsorption layer made of an ion exchange medium formed of a first porous material functionalized with basic or acidic functional groups, the basic or acidic functional groups generating a free base or free acid of the target salt by removing an acid or base component from the target salt; a sensitive layer located between the support substrate and the adsorption layer, the sensitive layer made of a second porous material functionalized to detect the free base or free acid of the target salt by a change in electrical conductivity; and a pair of electrodes connected to the sensitive layer and separated from each other by the sensitive layer.
[0092] Example 2: The sensor of any one of Examples 1 to 28, wherein the target salt is a salt of an alkaloid.
[0093] Example 3: The sensor of any one of Examples 1 to 28, wherein the target salt is a salt of an opiate.
[0094] Example 4: The sensor of any of Examples 1 to 28, wherein the target salt is fentanyl hydrochloride or carfentanil.
[0095] Example 5: The sensor according to any one of Examples 1 to 28, wherein the solid particles of the target salt have a particle size of about 0.1 μm to about 10 μm.
[0096] Example 6: The sensor of any one of Examples 1 to 28, wherein the support substrate is made of at least one of glass, silicon, alumina, sapphire, mica, quartz, or plastic.
[0097] Example 7: A sensor of any of Examples 1 to 28, wherein the first porous material is functionalized with a basic functional group to generate a free base of the target salt, and the second porous material is an acidic nanofiber functionalized to detect the free base.
[0098] Example 8: The sensor according to any one of Examples 1 to 28, wherein the basic functional group is a primary amino group, a secondary amino group, or a combination thereof.
[0099] Example 9: The sensor of any one of Examples 1 to 28, wherein the basic functional group is hexylamine, ethylethylamine, dimethylbutylamine, or any combination thereof.
[0100] Example 10: The sensor of any of Examples 1 to 28, wherein the first and second porous materials are formed from at least one of organic nanofibers, polymer nanofibers, carbon nanotubes, silicon nanowires, metal oxide nanowires, boron nitride nanotubes, aerogels, xerogels, highly porous ceramics, and metal-organic frameworks (MOFs).
[0101] Example 11: The sensor of any one of Examples 1 to 28, wherein the first porous material is a network of first organic nanofibers.
[0102] Example 12: The sensor of Example 11, wherein the first organic nanofiber is composed of a laminated molecule formed by the assembly and lamination of molecules, the laminated molecules being selected from the group consisting of 3,4,9,10-perylene-tetracarboxylic diimide, 3,4,9,10-perylene-tetracarboxylic dianhydride, perylene-3,4,9,10-tetracarboxylic-3,4-anhydride-9,10-imide, indolocarbazole derivatives, and oligomers composed of 3 to 9 carbazole derivative monomers, and further wherein at least a portion of the laminated molecules is functionalized with the basic functional group.
[0103] Example 13: The sensor of Example 11, characterized in that the first organic nanofiber is composed of a laminated molecule in which molecules having any one of the 12 molecular structures shown in the following chemical formulas I to XII are assembled and laminated.
[0104] [ka] (I)
[0105] [ka] (II)
[0106] [ka] (III)
[0107] [ka] (IV)
[0108] [ka] (V)
[0109] [ka] (VI)
[0110] [ka] (VII)
[0111] [ka] (VIII)
[0112] [ka] (IX)
[0113] [ka] (X)
[0114] [ka] (XI)
[0115] [ka] (XII)
[0116] Example 14: The sensor of Example 13, characterized in that the second organic nanofiber is composed of a laminated molecule in which molecules having either of the two molecular structures shown in the following chemical formulas XIII and XIV are assembled and laminated.
[0117] [ka] (XIII)
[0118] [ka] (XIV)
[0119] Example 15: The sensor of Example 14, characterized in that the molecules of the first organic nanofiber have the molecular structure shown in the above chemical formula X and the molecules of the second organic nanofiber have the molecular structure shown in the above chemical formula XIV, or the molecules of the first organic nanofiber have the molecular structure shown in the above chemical formula XI and the molecules of the second organic nanofiber have the molecular structure shown in the above chemical formula XIV, or the molecules of the first organic nanofiber have the molecular structure shown in the above chemical formula XII and the molecules of the second organic nanofiber have the molecular structure shown in the above chemical formula XIV.
[0120] Example 16: The sensor according to any one of Examples 1 to 28, wherein the adsorption layer has a thickness of 50 nm to 5 μm.
[0121] Example 17: The adsorption bed has a mass of 3 mm 2 The particle size is 0.1 μg to about 6 μg per 0.1 mm2. 2 ~10 mm 2 29. The sensor of any one of Examples 1 to 28,
[0122] Example 18: The sensor according to any one of Examples 1 to 28, wherein the adsorption layer is a porous material having an average pore size of 10 nm to 1 μm.
[0123] Example 19: The sensor according to any one of Examples 1 to 28, wherein the second porous material is made of a second organic nanofiber, the second organic nanofiber is composed of a laminated molecule formed by the assembly of molecules, and the laminated molecule is a molecule selected from the group consisting of substituted or unsubstituted 3,4,9,10-perylene-tetracarboxylic acid diimide, substituted or unsubstituted 3,4,9,10-perylene-tetracarboxylic acid dianhydride, substituted or unsubstituted perylene-3,4,9,10-tetracarboxylic acid-3,4-anhydride-9,10-imide, indolocarbazole derivatives, and oligomers composed of 3 to 9 carbazole derivative monomers.
[0124] Example 20: A sensor of any of Examples 1 to 28, characterized in that the second porous material is made of a second organic nanofiber, and the second organic nanofiber is composed of a laminated molecule in which molecules having either of the two molecular structures shown in the following chemical formulas XIII and XIV are assembled and laminated.
[0125] [ka] (XIII)
[0126] [ka] (XIV)
[0127] Example 21: The sensor of any of Examples 1 to 28, characterized in that the adsorption layer is directly connected to the sensitive layer.
[0128] Example 22: The sensor according to any one of Examples 1 to 28, wherein the sensitive layer has a thickness of 50 nm to 5 μm.
[0129] Example 23: The sensitive layer has a mass of 3 mm 2 The sensor according to any one of Examples 1 to 28, wherein the concentration is 0.1 μg to about 6 μg per sensor.
[0130] Example 24: A sensor of any of Examples 1 to 28, characterized in that the pair of electrodes are made of gold, titanium, indium tin oxide, indium zinc oxide, tungsten, aluminum, platinum, silver, copper, PEDOT:PSS, or some combination thereof.
[0131] Example 25: The sensor of any of Examples 1 to 28, wherein the pair of electrodes are separated from each other by a gap width of 50 nm to 100 μm, the interdigital gap width is 5 μm to 50 cm, and the width of the finger-like portion is 0.1 to 50 μm.
[0132] Example 26: The sensor of any of Examples 1 to 28, further comprising a housing surrounding the adsorptive layer, the sensitive layer, and the pair of electrodes.
[0133] Example 27: The sensor of any of Examples 1 to 28, further comprising an alarm means electrically connected to the electrode and configured to emit an alarm signal, the alarm signal being a tactile signal, a visual signal, an auditory signal, a display, or a combination thereof.
[0134] Example 28: The sensor of any one of Examples 1 to 28, further comprising a blower for blowing air onto the adsorption layer.
[0135] Example 29: A method for detecting solid particles of a target salt, the method comprising the steps of exposing an adsorbent layer to a gaseous medium containing particles of the target salt, the adsorbent layer comprising an ion exchange medium formed of a first multiporous material functionalized with basic or acidic functional groups, the basic or acidic functional groups being capable of removing an acid or base component from the target salt to generate a free base or free acid of the target salt, the free base or free acid of the target salt migrating by diffusion to a sensitive layer adjacent the adsorbent layer, the sensitive layer comprising a second multiporous material functionalized to detect the free base or free acid of the target salt, the free base or free acid of the target salt changing the electrical conductivity of the second multiporous material, the method comprising the steps of measuring the change in electrical conductivity of the sensitive layer using a pair of electrodes connected to and separated from each other by the sensitive layer.
[0136] Example 30: The method of any of Examples 29 to 58, wherein the gaseous medium comprises air.
[0137] Example 31: The method of any of Examples 29 to 58, wherein the free base is a condensed material, a vapor, or a gas.
[0138] Example 32: The concentration of the target salt in the gas medium is 0.1 mg / m 3 ~100 mg / m 3 59. The method of any of Examples 29 to 58, wherein
[0139] Example 33: The method of any of Examples 29 to 58, wherein the target salt is a salt of an alkaloid.
[0140] Example 34: The method of any of Examples 29 to 58, wherein the target salt is a salt of an opiate.
[0141] Example 35: The method of any of Examples 29 to 58, wherein the target salt is fentanyl hydrochloride or carfentanil.
[0142] Example 36: The method of any of examples 29 to 58, wherein the solid particles of the target salt have a particle size of about 0.1 μm to about 10 μm.
[0143] Example 37: The method of any of Examples 29 to 58, wherein the first porous material is functionalized with a basic functional group to generate a free base of the target salt, and the second porous material is an acidic nanofiber functionalized to detect the free base.
[0144] Example 38: The method of any of Examples 29 to 58, wherein the first and second porous materials are formed from at least one of organic nanofibers, polymer nanofibers, carbon nanotubes, silicon nanowires, metal oxide nanowires, BN nanotubes, aerogels, xerogels, highly porous ceramics, metal-organic frameworks (MOFs), glassy carbons, chalcopyrites, and chalcogenides.
[0145] Example 39: The method of any of Examples 29 to 58, wherein the first porous material is a network of first organic nanofibers and the second porous material is a network of second organic nanofibers.
[0146] Example 40: The method of Example 39, wherein the first organic nanofiber is composed of a laminated molecule formed by the assembly of molecules, the laminated molecules being selected from the group consisting of 3,4,9,10-perylene-tetracarboxylic diimide, 3,4,9,10-perylene-tetracarboxylic dianhydride, perylene-3,4,9,10-tetracarboxylic-3,4-anhydride-9,10-imide, indolocarbazole derivatives, and oligomers composed of 3 to 9 carbazole derivative monomers, and further characterized in that at least a portion of the laminated molecule is functionalized with the basic functional group.
[0147] Example 41: The method of any one of Examples 29 to 58, wherein the basic functional groups comprise primary amino groups, secondary amino groups, or a combination thereof.
[0148] Example 42: The method of any of Examples 29 to 58, wherein the basic functional group comprises hexylamine, ethylethylamine, dimethylbutylamine, or any combination thereof.
[0149] Example 43: The method of any one of Examples 29 to 58, wherein the first organic nanofiber is composed of a laminated molecule formed by assembling and stacking molecules having any one of the 12 molecular structures shown in the following chemical formulas I to XII.
[0150] [ka] (I)
[0151] [ka] (II)
[0152] [ka] (III)
[0153] [ka] (IV)
[0154] [ka] (V)
[0155] [ka] (VI)
[0156] [ka] (VII)
[0157] [ka] (VIII)
[0158] [ka] (IX)
[0159] [ka] (X)
[0160] [ka] (XI)
[0161] [ka] (XII)
[0162] Example 44: The method of Example 39, characterized in that the second organic nanofiber is composed of laminated molecules in which molecules having either of the two molecular structures shown in the following chemical formulas XIII and XIV are assembled and laminated.
[0163] [ka] (XIII)
[0164] [ka] (XIV)
[0165] Example 45: The method of Example 44, characterized in that the molecules of the first organic nanofiber have the molecular structure shown in chemical formula X above and the molecules of the second organic nanofiber have the molecular structure shown in chemical formula XIV above, or the molecules of the first organic nanofiber have the molecular structure shown in chemical formula XI above and the molecules of the second organic nanofiber have the molecular structure shown in chemical formula XIV above, or the molecules of the first organic nanofiber have the molecular structure shown in chemical formula XII above and the molecules of the second organic nanofiber have the molecular structure shown in chemical formula XIV above.
[0166] Example 46: The method of any one of Examples 29 to 58, wherein the adsorption layer has a thickness of 50 nm to 5 μm.
[0167] Example 47: The adsorption bed has a mass of 3 mm 2 59. The method of any of Examples 29 to 58, wherein the amount of the compound is from 0.1 μg to about 6 μg per unit area.
[0168] Example 48: The method of any of Examples 29 to 58, wherein the adsorption layer is porous with an average pore size between 10 nm and 1 μm.
[0169] Example 49: The method of Example 39, wherein the second organic nanofiber is composed of a laminated molecule formed by the assembly of molecules, and the laminated molecule is a molecule selected from the group consisting of substituted or unsubstituted 3,4,9,10-perylene-tetracarboxylic acid diimide, substituted or unsubstituted 3,4,9,10-perylene-tetracarboxylic acid dianhydride, substituted or unsubstituted perylene-3,4,9,10-tetracarboxylic acid-3,4-anhydride-9,10-imide, indolocarbazole derivatives, and oligomers composed of 3 to 9 carbazole derivative monomers.
[0170] Example 50: The method of Example 39, characterized in that the second organic nanofiber is composed of laminated molecules in which molecules having either of the two molecular structures shown in the following chemical formulas XIII and XIV are assembled and laminated.
[0171] [ka] (XIII)
[0172] [ka] (XIV)
[0173] Example 51: The method of any of Examples 29 to 58, wherein the sensitive layer has a thickness of 50 nm to 5 μm.
[0174] Example 52: The sensitive layer has a mass of 3 mm 2 59. The method of any of Examples 29 to 58, wherein the amount of the compound is from 0.1 μg to about 6 μg per unit area.
[0175] Example 53: The method according to any of Examples 29 to 58, wherein the adsorption layer is directly connected to the sensitive layer.
[0176] Example 54: The method of any of Examples 29 to 58, wherein the pair of electrodes is made of gold, titanium, indium tin oxide, indium zinc oxide, tungsten, aluminum, platinum, silver, copper, PEDOT:PSS, or some combination thereof.
[0177] Example 55: The method of any of Examples 29 to 58, wherein the pair of electrodes is separated from each other by a gap width of 50 nm to 100 μm.
[0178] Example 56: The method of any of Examples 29 to 58, wherein the free base of the target salt enhances the electrical conductivity of the second organic nanofibers of the sensitive layer.
[0179] Example 57: The method of any of Examples 29 to 58, further comprising the step of alerting the user that the target salt has been detected using a tactile signal, a visual signal, an auditory signal, a display, or a combination thereof.
[0180] Example 58: The method of any of Examples 29 to 58, further comprising the step of blowing the gaseous medium onto the adsorption bed using a blower.
[0181] The above detailed description has described the invention with reference to specific embodiments as illustrative examples. It should be understood, however, that various changes and modifications may be made without departing from the scope of the invention as set forth in the appended claims. The detailed description and the accompanying drawings are illustrative of the invention rather than limiting, and all such changes and modifications as have been described and are intended to be included within the scope of the invention.
Claims
1. 1. A sensor for detecting solid particles of a target salt, comprising: A support substrate; an adsorption bed comprising an ion exchange medium formed of a first porous material functionalized with basic or acidic functional groups, the basic or acidic functional groups capable of removing an acid or base moiety from the target salt to form a free base or free acid of the target salt; a sensitive layer located between the support substrate and the adsorbent layer, the sensitive layer comprising a second porous material functionalized to detect the free base or the free acid of the target salt by a change in electrical conductivity; A pair of electrodes in contact with and separated by the sensitive layer; Including a sensor.
2. 2. The sensor of claim 1, wherein the target salt is an alkaloid salt or an opiate salt.
3. 2. The sensor of claim 1, wherein the target salt is fentanyl hydrochloride or carfentanil.
4. The sensor of claim 1 , wherein the support substrate comprises glass, silicon, alumina, sapphire, mica, quartz, plastic, or a combination thereof.
5. 2. The sensor of claim 1, wherein the first porous material is functionalized with a basic functional group to generate a free base of the target salt, and the second porous material is an acidic nanofiber functionalized to detect the free base.
6. The sensor of claim 1 , wherein the basic functional group comprises a primary amino group, a secondary amino group, a tertiary amino group, or a combination thereof.
7. 2. The sensor of claim 1, wherein the basic functional group comprises hexylamine, ethylethylamine, dimethylbutylamine, or a combination thereof.
8. 2. The sensor of claim 1, wherein the first and second porous materials comprise organic nanofibers, polymer nanofibers, carbon nanotubes, silicon nanowires, metal oxide nanowires, boron nitride nanotubes, aerogels, xerogels, highly porous ceramics, metal organic frameworks (MOFs), glassy carbon, chalcopyrites, chalcogenides, or combinations thereof.
9. 10. The sensor of claim 1, wherein the first porous material is a network of first organic nanofibers and the second porous material is a network of second organic nanofibers.
10. 10. The sensor of claim 9, wherein the first organic nanofiber is comprised of a layered molecule selected from the group consisting of 3,4,9,10-perylene-tetracarboxylic diimide, 3,4,9,10-perylene-tetracarboxylic dianhydride, perylene-3,4,9,10-tetracarboxylic-3,4-anhydride-9,10-imide, indolocarbazole derivatives, and oligomers comprised of 3 to 9 carbazole derivative monomers, at least a portion of the layered molecule being further functionalized with the basic functional group.
11. 10. The sensor of claim 9, wherein the first organic nanofiber is composed of layered molecules having at least one of the following structures: 【Chemistry 1】 (I) 【Chemistry 2】 (II) 【Chemistry 3】 (III) 【Chemistry 4】 (IV) 【Chemistry 5】 (V) 【Chemistry 6】 (VI) 【Chemistry 7】 (VII) 【Chemistry 8】 (VIII) 【Chemistry 9】 (IX) 【Chemistry 10】 (X) 【Chemistry 11】 (XI) 【Chemistry 12】 (XII)
12. 12. The sensor of claim 11, wherein the second organic nanofiber is composed of layered molecules having at least one of the following structures: 【Chemistry 13】 (XIII) 【Chemistry 14】 (XIV)
13. 13. The sensor of claim 12, wherein the first organic nanofiber structure and the second organic nanofiber structure are X and XIV, XI and XIV, or XII and XIV, respectively.
14. 2. The sensor of claim 1, wherein the second porous material comprises a second organic nanofiber composed of layered molecules selected from the group consisting of substituted or unsubstituted 3,4,9,10-perylene-tetracarboxylic diimide, substituted or unsubstituted 3,4,9,10-perylene-tetracarboxylic dianhydride, substituted or unsubstituted perylene-3,4,9,10-tetracarboxylic-3,4-anhydride-9,10-imide, indolocarbazole derivatives, and oligomers composed of 3 to 9 carbazole derivative monomers.
15. The sensor of claim 1 , wherein the adsorptive layer and the sensitive layer each have a thickness of 50 nm to 5 μm.
16. The adsorption layer and the sensitive layer each have a mass of 3 mm 2 0.1μg to 6μg per 0.1 mm2 area 2 ~10mm 2 The sensor of claim 1 ,
17. The sensor of claim 1 , wherein the adsorbent layer is porous with an average pore size of 10 nm to 1 μm.
18. 2. The sensor of claim 1, wherein the adsorptive layer is in direct contact with the sensitive layer.
19. The sensor of claim 1 , wherein the pair of electrodes are separated by a gap width of 50 nm to 100 μm.
20. 1. A method for detecting solid particles of a target salt, comprising: exposing an adsorbent layer to a gaseous medium containing particles of a target salt, the adsorbent layer comprising an ion exchange medium formed of a first multiporous material functionalized with basic or acidic functional groups that strip an acid or base moiety from the target salt to produce a free base or free acid of the target salt, the free base or free acid of the target salt diffusing to a sensitive layer adjacent the adsorbent layer, the sensitive layer comprising a second multiporous material functionalized to detect the free base or free acid of the target salt, the free base or free acid of the target salt causing a change in electrical conductivity of the second multiporous material; measuring the change in electrical conductivity of the sensitive layer using a pair of electrodes in contact with and separated by the sensitive layer; A method comprising:
21. The method of claim 20 , wherein the gaseous medium comprises air.
22. The concentration of the target salt in the gas medium is 0.1 mg / m 3 ~100 mg / m 3 21. The method of claim 20, wherein the solid particles of the target salt have a particle size of about 0.1 μm to about 10 μm.
23. 21. The method of claim 20, wherein the target salt is fentanyl hydrochloride or carfentanil.
Citation Information
Patent Citations
Measuring free base concentration in industrial water
JP1980090852A
Gas sensor based on metal-carbon complexes
JP2017508965A
Electrochemical assays for the detection of opioids
JP2020518830A
Chemical Sensor Based on Highly Organized Single Walled Carbon Nanotube Networks
US20140197046A1
Capacitance spectroscopic method and electrode
US20160195520A1